Pengaruh Kualitas Pelayanan Dan Kepercayaan Terhadap Loyalitas Konsumen Dimediasi Kepuasan Konsumen Generasi Milenial Masa Pandemic Covid-19 (Survei Pengguna Tokopedia Generasi Milenial Jakarta Utara) - Koerniawan Hidajat; Ahmad Fahlevi (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2020)
This study aims to determine and explain the influence of service quality, service quality affects consumer loyalty, trust affects consumer loyalty, consumer satisfaction affects consumer loyalty, service quality affects consumer loyalty mediated by consumer satisfaction and trust affects consumer loyalty mediated by consumer satisfaction. This type of research uses explanatory quantitative research with survey methods. The results of the study show that service quality has a positive and significant effect on consumer loyalty, customer trust has a positive and significant effect on consumer loyalty, consumer satisfaction has a positive and significant effect on consumer loyalty, consumer satisfaction is able to indirectly affect service quality on consumer loyalty, consumer satisfaction is able to indirectly affect customer loyalty. indirectly affect customer confidence in consumer loyalty. Keywords: Service Quality, Customer Trust, Customer Satisfaction, Consumer Loyalty